2022
DOI: 10.3390/ijerph19042163
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting with the Life of Patients with Hemodialysis: Qualitative Meta-Synthesis Study of Life of Caregivers of Patients with Hemodialysis

Abstract: As the number of patients with hemodialysis (HD) continues to increase, so too does the number of people depending on caregivers. There is need to pay attention to the lives of caregivers of patients with HD, where sacrifices are forced. This study systematically reviewed and synthesized qualitative studies that explored the experiences of caregivers caring for patients with HD using the meta-synthesis method. We searched literature using four databases (i.e., PubMed, Excerpta Medica dataBASE, Cumulated Index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
3
2
0
Order By: Relevance
“…Similarly, a qualitative meta-synthesis by Kim and Lee revealed physical and emotional exhaustion among family caregivers when ignoring their own emotions. 23 This finding is also consistent with the finding of the study among Iranian family caregivers who experienced caregiving as progressive exhaustion. 7 Thus, an interdisciplinary team approach in healthcare, which includes nurses and social workers, must be expedited for early identification of potential psychosocial concerns to initiate advance care planning for patients and their family caregivers.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, a qualitative meta-synthesis by Kim and Lee revealed physical and emotional exhaustion among family caregivers when ignoring their own emotions. 23 This finding is also consistent with the finding of the study among Iranian family caregivers who experienced caregiving as progressive exhaustion. 7 Thus, an interdisciplinary team approach in healthcare, which includes nurses and social workers, must be expedited for early identification of potential psychosocial concerns to initiate advance care planning for patients and their family caregivers.…”
Section: Discussionsupporting
confidence: 89%
“…The suffering became apparent when they witnessed the suffering of their family member with burdening symptoms while making an effort to hide their own emotions. Similarly, a qualitative meta-synthesis by Kim and Lee revealed physical and emotional exhaustion among family caregivers when ignoring their own emotions 23. This finding is also consistent with the finding of the study among Iranian family caregivers who experienced caregiving as progressive exhaustion 7.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, carers worked to adapt to their situation by thinking about the value of life while remembering how important their role as a carer was. Showing similar results to this study, a study on the resilience of carers of people with hemodialysis revealed that they sought to find meaning in their lives and to accept their situation positively to cope with their condition(s) [29]. Therefore, we can provide programs that can help PWD or their families find the meaning of life and form a stronger attachment to life, along with interventions that can help them realise the value of life and view their situations positively.…”
Section: Discussionsupporting
confidence: 79%
“…The informal carers or partners reported attempting to understand the person with dementia, protect that person, and adapt to the situation by living a life of symbiosis with that person [29,35]. On the other hand, in this meta-synthesis, carers showed the will to build their own lives while acknowledging their lives as carers.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation